Pengaruh HCl terhadap Aktifasi Zeolit Alam Clipnotilolit-Ca Pada Penyerapan Pb(II) - Zilfa Zilfa; Upita Septiani; Mirawati Mirawati (Jurnal Riset Kimia, 2020)
Research about the effect of HCl on the activation of clinoptilolite-Ca natural zeolite on Pb(II) absorption has been done. The purpose of this study is to determine the capacity of zeolite clinoptilolite-Ca activation by HCl can be used as an adsorbent. For analysis of the adsorption we used AAS whereas for zeolite characterization were used XRF and XRD. The analysis parameters are the effect of HCl concentration, particle size, adsorbent mass, contact time, total solution volume, concentration of Pb(II), and PH solution. These parameters were studied to determine the optimum conditions in the adsorption process. The optimum conditions absorption of Pb(II) for the acid activation process shows that the zeolite clinoptilolite-Ca can be used as an absorbent. The adsorption results show that the value of Pb(II) capacity in the activation process with HCl of 0.2 N produces adsorption capacity of 0.0821 mg/g, for particle size 125 Âµm produces and adsorption capacity 0.0821 mg/g, for an adsorbent mass of 0.1 g produces an adsorption capacity of 0.5110 mg/g, for contact time of 10 minutes is 0.5662 mg/g, for a metal solution volume of 12.5 mL is 0.5493 mg/g, for the concentration of metal ion solution 40 mg/L is 2.608 mg/g, and at pH = 7 is 4.923 mg/g. The output of several parameters can be concluded that the adsorption capacity of zeolite clinoptilolite-Ca to the absorption of Pb(II) is 4.923 mg/g. Characterization of zeolite adsorbents with XRF and XRD shows that the zeolite used is zeolite clinoptilolite-Ca. Â Â